2015
DOI: 10.1007/s10072-015-2155-8
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in perimenopausal women

Abstract: Hormonal changes during the reproductive cycle are thought to account for the variation in migraine occurrence and intensity. Although the majority of women and the specialists treating them do not consider migraine as a component of the climacteric syndrome, many women, in fact, do experience migraine during perimenopause. If a woman already suffers from migraine, the attacks often worsen during menopausal transition. Initial onset of the condition during this period is relatively rare. Women with the premens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…An early stage that lasts 5 to 8 years, characterized by amenorrhea length more than 1 year, low estrogen levels and high FSH level. The late stage is characterized by stable low levels of ovarian hormones [92].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early stage that lasts 5 to 8 years, characterized by amenorrhea length more than 1 year, low estrogen levels and high FSH level. The late stage is characterized by stable low levels of ovarian hormones [92].…”
Section: Resultsmentioning
confidence: 99%
“…As perimenopause and menopause consist of several phases, each with a unique hormonal pattern, they all have a different effect on migraine. Another important factor is whether the menopause is naturally or artificially induced and whether HRT is used [92].…”
Section: Resultsmentioning
confidence: 99%
“…1 Migraines, insomnia, and depression are among the symptoms associated with surgical menopause. 1,2 It is known that surgical menopause is associated with a higher incidence of migraines, compared to natural menopause. 2 In addition, Ripa and associates reported that postmenopausal hormone-replacement therapy <HRT> was associated with worsening migraines.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is known that surgical menopause is associated with a higher incidence of migraines, compared to natural menopause. 2 In addition, Ripa and associates reported that postmenopausal hormone-replacement therapy <HRT> was associated with worsening migraines. 3 As shown by Chubaty et al, following surgical menopause, women receiving or not receiving HRT equally reported sleeping difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Many women experience migraine approaching menopause, but the trend of migraine symptoms may vary according to the different stages of the perimenopause. If a woman is already a migraineur subject, the attacks often worsen during both the early and late phases of menopausal transition, whereas an onset of migraine is quite rare[ 1 ]. According to some authors, women with premenstrual syndrome (PMS) before menopause have an increased prevalence of migraine in late menopausal transition, and a subsequent reduction of the attacks in postmenopause[ 2 ].…”
mentioning
confidence: 99%